On the genus Habrobathynella Schminke, 1973 (Crustacea, Malacostraca, Bathynellacea), with description of three new species from India - Shaik, Shabuddin; Reddy, Yenumula Ranga (Zootaxa, 2018)
The genus Habrobathynella Schminke, 1973 contains 16 species, 2 from Madagascar and 14 from the peninsular India. This is a remarkably species-rich genus when compared to the three other genera of the family Parabathynellidae known from India: Atopobathynella Schminke, 1973 (5 spp.), Chilibathynella Noodt, 1964 (1 sp.), and Parvulobathynella Schminke, 1973 (3 spp.). This paper provides a monographic treatment of Habrobathynella together with a detailed illustrated account of three new cavernicolous species, viz. Habrobathynella bose n. sp., Habrobathynella ernstmayr n. sp. and Habrobathynella raman n. sp., from the States of Andhra Pradesh and Telangana, India. For each of the already described species, the following details are provided: reference to original description, diagnosis, type data, type locality, distribution, ecology, co-occurrence with other species and remarks on taxonomic affinity. Distribution maps and a dichotomous key for identification of all species in Habrobathynella are provided. We also include a brief note on the biogeography and conservation status of the Indian bathynellaceans.